2018
DOI: 10.3177/jnsv.64.99
|View full text |Cite
|
Sign up to set email alerts
|

Current Vitamin D Status in Healthy Japanese Infants and Young Children

Abstract: This study aimed to characterize serum 25-hydroxyvitamin D (25OH-D) values among Japanese children aged ≤48 mo. The study included 290 healthy infants and young children aged 0-48 mo (males/females=166/124) living in Shizuoka or Tokyo. The subjects were divided into three groups by age (Low Age: 0-5, Middle Age: 6-15, High Age: 16-48 mo). The vitamin D deficient state was defined as 25OH-D <12 ng/mL, the insufficient state as 12-20 ng/mL, and the sufficient state as >20 ng/mL. The seasonal variation of serum 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Previous studies of healthy young children have reported higher prevalence estimates of 13.6% in Kenya, 15.0% in Uganda, and 25.8% in Nigeria [4,8,15]. Prevalence estimates were also higher in young children from other continents, including estimates of 15% in the USA, S7 14% in Japan, and 11% in China [34][35][36]. Vitamin D deficiency is also more prevalent in northern African countries [2], and the higher vitamin D status observed in our study might be explained by differences in latitude, geography, skin pigmentation, clothing coverage, and religious and cultural practices across Africa [37].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies of healthy young children have reported higher prevalence estimates of 13.6% in Kenya, 15.0% in Uganda, and 25.8% in Nigeria [4,8,15]. Prevalence estimates were also higher in young children from other continents, including estimates of 15% in the USA, S7 14% in Japan, and 11% in China [34][35][36]. Vitamin D deficiency is also more prevalent in northern African countries [2], and the higher vitamin D status observed in our study might be explained by differences in latitude, geography, skin pigmentation, clothing coverage, and religious and cultural practices across Africa [37].…”
Section: Discussionmentioning
confidence: 91%
“…However, a single study in Malawian pre-school children reported an increase in 25(OH)D levels with age; however, this study was small (n=21) and included infants of mothers living with HIV in Malawi [6]. Studies from high-income countries have reported an increase in 25(OH)D levels with age, but children in these studies received vitamin D supplementation or fortification [34,35,40]. In a meta-analysis of previous studies from Africa, children had higher vitamin D status than adults in African populations [2] possibly due to increased time spent outdoors.…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin D Status in Different Months from 2017 to 2020 Shizuoka (35.2°N, 138.4°E) and Tokyo (35.4°N, 139.4°E) and found that serum 25(OH)D levels were lower in winter and spring than in summer and autumn 20. Home confinement led to an increase in the proportion of children with vitamin D deficiency between March and June 2020 compared to the same month in previous years.…”
mentioning
confidence: 96%
“…Recent study in Japan by Nakano et al also showed similar results with vitamin D levels less than 20ng/ml in 75% of the infants. 18 Study on healthy breastfed infants in Delhi (North India) showed a prevalence of 86.5%. 19 Food fortification and targeted Vitamin D supplementation policies are recommended when the public health convention or the disease burden is >20%.…”
Section: Resultsmentioning
confidence: 99%